Enhanced Laptop Recommendation System Using Tsukamoto Fuzzy Logic - Nasrullah, Asmaul Husnah; Adiba, Fhatiah; Anastasia, Tezza; Farghina, Syakira Ayma; Akbar, Muh. (CV. Digital Innovation, 2024)
One of the most popular and rapidly growing needs among the general public is laptops. Currently, there are many types of laptops with varying features, and not everyone knows the advantages and disadvantages of each type. The purpose of this research is to develop and build a Fuzzy inference system that applies the Tsukamoto method. This is to address issues in providing unclear or inaccurate services to customers during the laptop sales process. By developing a recommendation system that can provide guidance or suggestions in purchasing a laptop based on interest and needs in searching for references, and the type of laptop that meets the criteria. The decision to purchase a laptop uses parameters such as screen size, RAM capacity, SSD capacity, and price. The implementation of the Fuzzy Tsukamoto method for providing laptop purchase recommendations is able to give good recommendations.